Integração geológico-geofísica para caracterização de plútons graníticos no domínio Erepecuru-Trombetas, Província Amazônia Central, Noroeste do Pará - LEAL, Rafael Estumano (2019)
The granitic rocks of the northwestern of Pará state are part of an expressive Orosirian volcano-plutonic association of the Amazon Craton. The area of this study is located in the southwestern of the Erepecuru-Trombetas Domain, in southern Guayana Shield, northwest of the Pará state. Most of the granitic bodies are grouped in the Mapuera Intrusive Suite, whose the age is established around 1.89 to 1.87 Ga. This study was conducted in a granitic body which outcrops in the central portion of this domain, correlated to that suite. The petrographic analysis allowed to distinguish five facies in this body, the northern comprises predominantly sienogranites and southern portion, is composed by monzo- to granodiorites, which have distinct geophysical patterns, and represent, respectively, the lithogeophycal units A (amphibole-biotite syenogranite and biotite syenogranite ) and B (amphibole-biotite monzo- to granodiorite it). The compositional variations and distinct geophysical signatures observed put into question the contemporaneity of these rocks and if they were formed by the same magmatic event or they are representatives of distinct magmatic events. Geochronological study was conducted by Pb-evaporation on zircon in representative samples of the lithgeophysical units A and B, respectively, an amphibole-biotite syenogranite and an amphibole-biotite monzogranite. The ages obtained were 1977 ± 4 Ma (MSWD = 2.7) and 1982 ± 9 Ma (MSWD = 11), which overlap within the errors, and this results showed that the two samples come from the same plutonic body. In other words, the lithgeophysical units A and B do not represent distinct magmatic bodies. Therefore, differences in airborne geophysical signature result of composicional differences of petrographic facies. These ages also revealed that the dated body does not belong to Mapuera Intrusive Suite. It can be correlated to older granitic bodies that have been mapped in Amazonas and Roraima states, and in the Tapajós Domain, in Pará state.